Future Learning Environments for Tomorrow's Schools - Shimon Amar; Netanel Bar David (European Scientific Journal, ESJ, 2017)
Teachers who want to prepare their students to cope with an unknown future, must equip them with a set of competencies that are essential for success in society in general and in any enterprise or organizational unit. Therefore, in today's reality, real-life scenarios should dictate the pedagogy and the design of learning environments that will meet the standards of modern working environments. In this paper, we attempt to reexamine content, pedagogy and learning environments in the current era. Based on our experience, we recommend that educational institutions adapt their classrooms by turning them into unique learning environments which will allow for a pedagogy that combines content which has been adapted to the 21st century with advanced and innovative technology in the most appropriate way for acquiring the necessary skills. The goal is that eventually educational systems will affect the real world by introducing innovative pedagogies and learning environments which will make an impact on working environments. This paper focuses on the work that has been carried out over the past three years geared at proposing new characteristics for learning environments in colleges of education.